Tax Management Analysis At PT Sumber Usaha Nusantara - Anggi Tiara Sari; Irawan Irawan; Pipit Buana Sari (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze the implementation of tax management at PT. Sumber Usaha Nusantara, a company engaged in supplying and exporting fishery products, particularly seafood such as soft shell crab, mud crab, and shrimp. This study used a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation studies. The results indicate that the company has implemented effective tax management, encompassing tax planning, implementation, and control, thus maintaining tax compliance through timely tax reporting, calculation, and payment. The implementation of tax management also enables the company to manage its tax burden efficiently and legally by utilizing available tax facilities. This study recommends that the company improve the competence of its tax staff, strengthen internal controls, and optimize tax facilities. Further research is recommended to examine the effect of tax management on the company's financial performance.